Literature Review: Correlation Between Mother’s Knowledge of Nutrition and Stunting Incidence in Children - Fitriyana Wulandari; Nur Juliana; Elna Sari; Endang Sri Mulyawati L (Politeknik Karya Persada Muna, 2022)
Background: Stunting is a condition of failure to thrive in children under five years old (in infants under five years old) caused by chronic malnutrition so that children are too short for their age. One of the factors that cause stunting is mother's knowledge about nutrition due to lack of information. The purpose of this study was to determine the relationship between maternal knowledge about nutrition and the incidence of stunting in children. Methods: This study uses a literature review method. This study uses Google Scholar to search electronic databases and filtering was carried out in the last 5 years from 2018-2022. This review begins by identifying keywords and their synonyms in several appropriate and relevant databases. The keywords used are knowledge of mothers, stunting, children, and nutrition. The journal searches that were successfully obtained were 44 journal articles so that 20 Indonesian and English journal articles were screened. Results: Based on the screening results, there were 17 journal articles showing that there was a relationship between mother's knowledge of stunting in children, while 3 journals showed that there was no relationship between mother's knowledge of stunting in children. Conclusion: The knowledge of parents, especially mothers, about good nutrition can prevent stunting in children. This is very important to support nutritional status so that children's quality of life is better. Keywords: Stunting, children, mother's knowledge, nutrition